Chiral copper-hydride nanoclusters: synthesis, structure, and assembly. Issue 11 (22nd February 2023) - Wang, Lin; Yan, Xiaodan; Tian, Guolong; Xie, Zhenlang; Shi, Shanshan; Zhang, Yuhao; Li, Simin; Sun, Xueli; Sun, Jing; He, Jinlu; Shen, Hui
Abstract : Novel copper-hydride nanoclusters of [Cu14 ( t BuS)3 (PPh3 )7 H10 ] + have been prepared. The cluster exhibits intrinsic chirality and helix assembling structures. Abstract : An effective strategy is developed to synthesize a novel and stable layered Cu nanocluster using a one-pot reduction method. The cluster, with a molecular formula of [Cu14 ( t BuS)3 (PPh3 )7 H10 ]BF4 which has been unambiguously characterized by single crystal X-ray diffraction analysis, exhibits different structures from previously reported analogues with core–shell geometries. In the absence of chiral ligands, the cluster displays intrinsic chirality owing to the non-covalent ligand–ligand interactions ( e.g., C–H⋯Cu interactions and C–H⋯π interactions) to lock the central copper core. The interlacing of chiral-cluster enantiomers forms a large cavity, which lays the foundation for a series of potential applications such as drug filling and gas adsorption. Moreover, the C–H⋯H–C interactions of phenyl groups between different cluster moieties promote the formation of a dextral helix and realization of the self-assembly of nanostructures.